Analysis of the policies and constraints limiting the aquaponics industry in Portugal - Mata, F. (2024)
Aquaponics is an innovative and potentially sustainable method of producing vegetables and fish, enabling local, inland fish production, and vegetable production without the need for artificial fertilization. With the aim to analyze the potential development of commercial aquaponics in Portugal, a group of Portuguese stakeholders and experts were interviewed to capture their understanding of the challenges faced by the emerging Portuguese aquaponics sector. The paper evaluates and discusses the main issues experienced by stakeholders, proposing solutions to overcome barriers and restrictions. Legal and administrative barriers were identified, and it is recognized that aquaponics requires its own legal and administrative framework. Bureaucracy is duplicated in licensing processes, authorizations for sale, and permits. Exotic fish species, such as tilapia (Tilapia spp.) face legal barriers to their use in aquaculture. The freshwater aquaculture species to consider for integration into aquaponics systems are largemouth bass (Micropterus salmoides), pikeperch (Sander lucioperca), and eel (Anguilla anguilla). To address barriers to the organic certification of aquaponics products, producers need to collaborate and establish their own certification schemes.